Penerapan Terapi Progressive Muscle Relaxation terhadap Kecemasan Pre Operasi Sectio Caesarea di RSUD Kajen Kabupaten Pekalongan - Rizki Nurcahyati; Dyah Restuning Prihati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Sectio Caesarea is a major surgical procedure that often causes anxiety in preoperative patients. Unmanaged anxiety can negatively affect patients’ physiological and psychological conditions and influence their readiness for surgery. One non-pharmacological intervention that nurses can apply to reduce anxiety is Progressive Muscle Relaxation (PMR) therapy, a relaxation technique performed by systematically tensing and relaxing muscle groups to achieve a relaxed state. Methods: This study used a descriptive method with a case study approach employing a one group pre-test and post-test without control design. The subjects consisted of five preoperative Sectio Caesarea patients who met the inclusion criteria. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the PMR intervention. The PMR therapy was administered twice, namely on the night before surgery and in the morning before the patient was transferred to the operating room, with a duration of approximately 20 minutes per session. Results: The results showed that prior to the PMR intervention, all respondents were in the moderate anxiety category. After the PMR intervention, anxiety levels decreased in all respondents to the mild anxiety category, as indicated by a consistent reduction in HRS-A scores for each patient.